Identification of a novel small molecule that inhibits deacetylase but not defatty-acylase reaction catalysed by SIRT2. (23rd April 2018) - Kudo, Norio; Ito, Akihiro; Arata, Mayumi; Nakata, Akiko; Yoshida, Minoru
Abstract : SIRT2 is a member of the human sirtuin family of proteins and possesses NAD + -dependent lysine deacetylase/deacylase activity. SIRT2 has been implicated in carcinogenesis in various cancers including leukaemia and is considered an attractive target for cancer therapy. Here, we identified NPD11033, a selective small-molecule SIRT2 inhibitor, by a high-throughput screen using the RIKEN NPDepo chemical library. NPD11033 was largely inactive against other sirtuins and zinc-dependent deacetylases. Crystallographic analysis revealed a unique mode of action, in which NPD11033 creates a hydrophobic cavity behind the substrate-binding pocket after a conformational change of the Zn-binding small domain of SIRT2. Furthermore, it forms a hydrogen bond to the active site histidine residue. In addition, NPD11033 inhibited cell growth of human pancreatic cancer PANC-1 cells with a concomitant increase in the acetylation of eukaryotic translation initiation factor 5A, a physiological substrate of SIRT2. Importantly, NPD11033 failed to inhibit defatty-acylase activity of SIRT2, despite its potent inhibitory effect on its deacetylase activity. Thus, NPD11033 will serve as a useful tool for both developing novel anti-cancer agents and elucidating the role of SIRT2 in various cellular biological processes. This article is part of a discussion meeting issue 'Frontiers in epigenetic chemical biology'.